KAJIAN ETNOBOTANI TANAMAN SINGKONG YANG BERPOTENSI SEBAGAI OBAT OLEH MASYARAKAT KABUPATEN BONDOWOSO - Nafilah Nafilah; Iis Nur Asyiah; Kamalia Fikri (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2017)
Abstract: Bondowoso is one of regencies in East Java which is famous with cassava production. The abundance of the crop is caused by a very supportive natural condition. The abundance of cassava plants in Bondowoso Regency is really helpful to support the fulfillment needs of the community, especially the utilization as a traditional medicine that is trusted by the community as an alternative medicine that is easy and cheap also healthy. The research method used is direct observation with sampling using Purposive Sampling and Snowball Sampling. The results showed that there are 10 types of cassava plant utilization that has potential as medicine, including blood booster, infant massage, Astomach medication, sondhep medicine (angina/sitting wind), wound medicine, bone strengthening drink, bone fracture, travel ailment, kidney disease and stomach ailment. Keywords: Ethnobotany; Traditional Medicine; Cassava